Interaction of Demonstration Learning Model with Learning Motivation in The Development of Critical Thinking Skills in Elementary School Mathematics Learning in Ngrampal-Sragen - Saraswati, Dwi; Riyadi, Riyadi; Kurniawan, Sandra Bayu (Social, Humanities, and Educational Studies (SHES): Conference Series, 2025)
The development of critical thinking skills requires the selection of learning models that can appropriately achieve learning goals. The purpose of the study was to prove the interaction between demonstration learning model with learning motivation towards the development of critical thinking skills in mathematics learning. This type of research is quasi-experimental, using quantitative data analysis. The study population is the third grade elementary school students in the district Ngrampal, Sragen. Sampling using cluster random sampling. Data collection with tests. The data were analyzed by variance analysis test of two different cell paths and further test of variance analysis. The results showed a summary of Anava obtained Fhitung(11.844) > Ftable (3.91), can be interpreted there is an interaction between the demonstration learning model with learning motivation. Variance follow-up test results, namely: marginal mean for criteria: High 85.37, medium 84.77, and low 83.77 and the results of comparative analysis between cell lines, namely: , Fcount (11.982) > Ftable (6.08); , Fcount (11.946) > Ftable (6.08); , Fcount (57,639) > Ftable (6.08), it can be interpreted that motivation for all criteria has an influence on the demonstration learning model in the development of critical thinking skills. The conclusion of the study is that there is an interaction between the demonstration learning model with learning motivation in the development of critical thinking skills.